Regional hyperperfusion in cognitively normal APOE ε4 allele carriers in mid-life: analysis of ASL pilot data from the PREVENT-Dementia cohort. Issue 8 (25th June 2020) - McKiernan, Elizabeth Frances; Mak, Elijah; Dounavi, Maria-Eleni; Wells, Katie; Ritchie, Craig; Williams, Guy; Su, Li; O'Brien, John
Abstract : Background: Regional cerebral hypoperfusion is characteristic of Alzheimer's disease (AD). Previous studies report conflicting findings in cognitively normal individuals at high risk of AD. Understanding early preclinical perfusion alterations may improve understanding of AD pathogenesis and lead to new biomarkers and treatment targets. Methods: 3T arterial spin labelling MRI scans from 162 participants in the PREVENT-Dementia cohort were analysed (cognitively normal participants aged 40–59, stratified by future dementia risk). Cerebral perfusion was compared vertex-wise according to APOE ε4 status and family history (FH). Correlations between individual perfusion, age and cognitive scores (COGNITO battery) were explored. Results: Regional hyperperfusion was found in APOE ε4 +group (left cingulate and lateral frontal and parietal regions p<0.01, threshold-free cluster enhancement, TFCE) and in FH +group (left temporal and parietal regions p<0.01, TFCE). Perfusion did not correlate with cognitive test scores. Conclusions: Regional cerebral hyperperfusion in individuals at increased risk of AD in mid-life may be a very early marker of functional brain change related to AD. Increased perfusion may reflect a functional 'compensation' mechanism, offsetting the effects of early neural damage or may itself be risk factor for accelerating spread of degenerative pathology.